Pengawasan Penggunaan Alat Penangkapan Ikan Oleh Polisi Perairan di Nagari Air Bangis Pasaman Barat - Purnama Sitinjak; Adil Mubarak (Jurusan Ilmu Administrasi Negara, 2019)
The implementation of Minister of Maritime Affairrs and Fisheries Regulation number 71 of 2016 it has not been effective. Some fishermen experience various kinds of problems and reject the existence of these regulations. One of the most central areas is Nagari Air Bangi West Pasaman. Fishermen in Air Bangis participated in the demonstration for the continuation of this Ministerial Regulation. This is Because the majority of fishermen use mesh sizes and lamp sizes that are not in accordance with the contents of the Minister’s rules. So that the Aquatic Police continue to exist to uphold the existing rules and roam about conducting surveillance. This study aims to determine the implementation of supervision by the Aquatic Police on the use of fishing gear in the Nagari Ai Bangis West Pasaman. This research is a qualitative research with descriptive method. The research informants were determined by purposive sampling and snowball sampling techniques namely Aquatic Police, West Pasaman Fisheries Service, Nagari, Owner of Bagan and fishing communities. The results of the study show that the implementation of supervision has not been carried out to the maximum that is targeted. This happened because there were still many obstacles encountered in the field such as the lack of personnel, facilities and infrastructure and the budget. Efforts were made to propose an increase in the number of personnel to the police chief, using the facilities and infrastructure as well as possible, to disseminate to the fishing community Development